National health under socialism or the B.M.A.? : A National Crisis (1930)
1930 1930 1930s 2 pages F.G. BUSHNELL Critical NATIONAL HEALTH UNDER SOCIALISM OR THE B.M.A.? A National Crisis 1930 There is a secret but general attack on the Socialisation of Medicine and its control by the workers by immense forces who desire to influence the Ministry of Health and the T.U.C. and Its approved Societies in favour of the proposals of the B.M.A. for the extension of medical and maternity benefits of the National Health Insurance Acts on a contributory insurance basis, together with a development of the voluntary hospital contributory scheme. (See B.M.J., April 26, 1930, 19, 1930, June 29, 1929). These proposals are in direct opposition to the I.L.P. National Health Policy as outlined at its Birmingham Conference in April, 1930 (resolution 115), whereby the medical and allied workers departments, services and institutions would be unified, socialised, humanised, rationalised and nationalised (not bureaucratised). They are in direct opposition both to the Labour movement’s policy in regard to health (see "The Labour Movement and Preventive and Curative Medical Services, T.U.C. and L.P.") and its policy in regard to hospitals, ("The Labour Movement and the Hospital Crisis" T.U.C. and L.P.) and to the Royal Commission’s findings on Insurance Committees and with Approved Societies connected with industrial Assurance Companies. At this dangerous crisis for the lives and health of the workers the Independent Labour Party resolution in favour of the formation of Workers’ Health Committees to resist this attack and achieve socialisation Is vital and essential. The B.M.A. proposals are merely a reformist and opportunist move forced upon the medical profession by the utter chaos, inadequacy, inefficiency and inhumanity of the present arrangements for medical treatment, together with a keen eye to their professional profits. The estimated cost to the community of the B.M.A. general medical service scheme is from £10,890,000 and of the B.M.A. Maternity Scheme £2,022,869 upwards. The cost of the B.M.A. hospital proposals is unknown. Its acceptance by the workers would be (1) A repudiation of the health and hospital policy of the Labour movement, which declared for free, adequate, efficient and humane medical aid and institutions through a unified public paid medical and allied service of the Ministry of Health (vide the Labour Party’s "statements" on the "Preventive and curative medical services" and the "Hospital crisis"); (2) The consolidation of the present powerful capitalistic, financial, bureaucratic and professional interests at the further expense of the already exploited lives and health of the workers, and further incentive to medical workers to live for the gain of profits and not service, by the extension of the present system of payment "per capita" under the National Health Insurance Acts, without adequate control by the insured person; (3) The multiplication and not the unification of the branches of the medical services, which would be still under different, departmental, sectional and voluntary authorities and not under the control of the workers, either the insured or the uninsured. 1 292/840/1/25